Small-Molecule Activation by Low-Coordinated Germanium Compounds - Sasamori, Takahiro (Synlett, 2024)
We have been interested in the differences between the properties of low-coordinated carbon compounds and their heavier homologues based on elements of group 14, e.g., Si and Ge. Fundamental research on the synthesis and characterization of divalent and multiply bonded compounds of heavier group 14 elements has led to a variety of isolated low-coordinated species of heavier group 14 elements that can replace transition metals in small-molecule transformations. We have focused on low-coordinated germanium compounds with double or triple bonds between germanium atoms, as well as germanium-containing aromatic compounds. Once isolated, the reactivity of these low-coordinated germanium compounds was examined with regard to small-molecule activation. In this account, the reactivity patterns of these compounds will be described.1 Introduction2 1,2-Dibromodigermenes and Bromogermylenes3 Digermynes4 1,2-Digermacyclobutene5 1,3-Digerma-2-silaallene6 Digerma-Aromatic Compounds7 Germanium-Catalyzed Cyclotrimerization of Alkynes8 Summary
Keywords: germanium; main-group elements; small-molecule activation; digermene; digermyne; digermabenzene